Osmotic demyelination syndrome caused by normal saline correction in a patient admitted for gastric ulcer bleeding. Issue 2 (April 2014) - Yen, H.-W.; Wang, J. P.; Lin, P.-Y.; Lai, M.-Y.; Lirng, J.-F.; Chao, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> A 61-year-old male had osmotic demyelination syndrome caused by rapid correction of gastric ulcer bleeding and vomiting related hyponatraemia with normal saline. It is rare to see severe hyponatraemia caused by gastric ulcer bleeding and vomiting. Hypokalaemia may be the determinant predisposing factor. There was no specific brain image finding until 17 days after the initial clinical presentation of this disease. Brain diffusion weighted MRI series did not help for the early diagnosis in this case. Outcome of this case may be more favourable if we corrected his hyponatraemia with half-saline or other hypotonic saline and close monitored serum sodium level, and relowered with dextrose water and desmopressin once we observed that the correction rate of hyponatraemia was beyond the recommended rate.